(untitled) (Journal of Science and Technology, 2016)
Assessment of wood density using indirect method with the pilodyn was carried out on 33 provenances of grand for (Abiep grandis) grown at two Sites-Wark and Drummond Hill in Britain. Initial evaluation to deter-mine the need for multiple readings on individual trees produced repeatability value of 0.74 suggesting that a single measurement will suffice. A two-way nested ANOVA model on provenance variation indicated highly significant differences between provenances and sites. The site with a high potential for growth, Drummond Hill, produced wood of relatively lower density than Wark. This suggested that site characteristics may be a limitation on the production of high-density wood in grand fir. However, the provenances 12002 and 12042 have comparatively higher wood density irrespective of the site on which they are grown.